Installing trim [ - Savage, Craig , 1947-; Savage, Craig , 1947-; Williams, Nathan , (Vocalist) (A Fine homebuilding video workshop, 2003)
Craig Savage shows how to install door and window casings, baseboard, and crown moldings.